2000
DOI: 10.1038/78630
|View full text |Cite
|
Sign up to set email alerts
|

The mammary gland iodide transporter is expressed during lactation and in breast cancer

Abstract: The sodium/iodide symporter mediates active iodide transport in both healthy and cancerous thyroid tissue. By exploiting this activity, radioiodide has been used for decades with considerable success in the detection and treatment of thyroid cancer. Here we show that a specialized form of the sodium/iodide symporter in the mammary gland mediates active iodide transport in healthy lactating (but not in nonlactating) mammary gland and in mammary tumors. In addition to characterizing the hormonal regulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
436
5
15

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 431 publications
(482 citation statements)
references
References 35 publications
26
436
5
15
Order By: Relevance
“…Unlike in non-lactating mammary gland tissue, in transgenic mice bearing experimental breast cancers triggered by Erb-B2/neu and ras oncogenes, functional expression of NIS significantly increases [1]. In the same study, human breast cancer specimens were also analyzed, and an increased NIS expression was detected in human invasive breast cancer and ductal carcinoma in situ, as compared to no expression of NIS in healthy breast samples obtained from reductive mammoplasty operations [1].Recent studies with an ERa+ mammary cell line model, MCF-7, have led to the identification of additional hormones or ligands that control transcriptional regulation of NIS. In this cell line, the symporter gene was shown to be inducible in response to 9-cis-retinoic acid (9cRA) and all-trans-retinoic acid (tRA), ligands that were previously 0006-291X/$ -see front matter Ó…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…Unlike in non-lactating mammary gland tissue, in transgenic mice bearing experimental breast cancers triggered by Erb-B2/neu and ras oncogenes, functional expression of NIS significantly increases [1]. In the same study, human breast cancer specimens were also analyzed, and an increased NIS expression was detected in human invasive breast cancer and ductal carcinoma in situ, as compared to no expression of NIS in healthy breast samples obtained from reductive mammoplasty operations [1].Recent studies with an ERa+ mammary cell line model, MCF-7, have led to the identification of additional hormones or ligands that control transcriptional regulation of NIS. In this cell line, the symporter gene was shown to be inducible in response to 9-cis-retinoic acid (9cRA) and all-trans-retinoic acid (tRA), ligands that were previously 0006-291X/$ -see front matter Ó…”
mentioning
confidence: 94%
“…I À in milk is used by the newborn in thyroid hormone biosynthesis, and thus it plays an essential role in post-natal development of skeletal muscles, nervous system, and lungs [2]. In vivo experiments in mice have previously demonstrated that in normal physiology, NIS expression is strictly linked to mammary development in gestation, and to lactation [1]. Non-lactating mammary gland tissue in female mice does not express NIS unless animals receive subcutaneous oxytocin treatments for three consecutive days.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations